Steroidal alkaloids defence metabolism and plant growth are modulated by the joint action of gibberellin and jasmonate signalling. Issue 3 (3rd December 2021) - Panda, Sayantan; Jozwiak, Adam; Sonawane, Prashant D.; Szymanski, Jedrzej; Kazachkova, Yana; Vainer, Andrii; Vasuki Kilambi, Himabindu; Almekias‐Siegl, Efrat; Dikaya, Varvara; Bocobza, Samuel; Shohat, Hagai; Meir, Sagit; et al.
Summary: Steroidal glycoalkaloids (SGAs) are protective metabolites constitutively produced by Solanaceae species. Genes and enzymes generating the vast structural diversity of SGAs have been largely identified. Yet, mechanisms of hormone pathways coordinating defence (jasmonate; JA) and growth (gibberellin; GA) controlling SGAs metabolism remain unclear. We used tomato to decipher the hormonal regulation of SGAs metabolism during growth vs defence tradeoff. This was performed by genetic and biochemical characterisation of different JA and GA pathways components, coupled with in vitro experiments to elucidate the crosstalk between these hormone pathways mediating SGAs metabolism. We discovered that reduced active JA results in decreased SGA production, while low levels of GA or its receptor led to elevated SGA accumulation. We showed that MYC1 and MYC2 transcription factors mediate the JA/GA crosstalk by transcriptional activation of SGA biosynthesis and GA catabolism genes. Furthermore, MYC1 and MYC2 transcriptionally regulate the GA signalling suppressor DELLA that by itself interferes in JA‐mediated SGA control by modulating MYC activity through protein–protein interaction. Chemical and fungal pathogen treatments reinforced the concept of JA/GA crosstalk during SGA metabolism. These findings revealed the mechanism of JA/GA interplay in SGA biosynthesis to balance the cost of chemical defence with growth.